PROMOTING CLIMATE JUSTICE THROUGH SMR LICENSING IN THE UNITED STATES AND CANADA: LEGAL COMPARISON AND LESSONS FOR VIETNAM AND DEVELOPING COUNTRIES - Le Minh, Nhut; Huy, Tran Quang (UI Scholars Hub, 2026)
Climate justice is an issue raised in Vietnam and many developing countries around the world due to the increasing number of serious climate change events in recent years. For this reason, energy transition is chosen as one of the solutions for climate justice promotion in Vietnam, as well as in other developing countries. Across the options, Small modular reactor (SMR) investment is under significant consideration for climate justice promotion in Vietnam and the developing countries. SMR can ensure that every person has access to clean energy while protecting the environment. However, developing SMR requires the harmonisation between innovation and nuclear safety when licensing SMR. For this reason, this study aims to develop recommendations for promoting climate justice by establishing regulations and rules governing the SMR licensing procedure. To realise the target, this study uses a legal comparative methodology to explain the rules and laws governing SMR licenses in the United States of America and Canada and how they promote climate justice. The findings show that flexibility is the core component of SMR licensing that contributes to climate justice. On this basis, the study further recommends legal solutions to promote climate justice in Vietnam and other developing countries through SMR licensing.